Comparison of trauma management between two major trauma services in Riyadh, Kingdom of Saudi Arabia and Melbourne, Australia - Peter Cameron; Mark Fitzgerald; Arul Earnest; Mohammad Alsenani; Faisal A Alaklobi; Jane Ford; Waleed Hashem; Sharfuddin Chowdhury; Ahmed Alenezi (BMJ Open)
Introduction The burden of injury in the Kingdom of Saudi Arabia (KSA) has increased in recent years, but the country has lacked a consistent methodology for collecting injury data. A trauma registry has been established at a large public hospital in Riyadh from which these data are now available.Objectives We aimed to provide an overview of trauma epidemiology by reviewing the first calendar year of data collection for the registry. Risk-adjusted analyses were performed to benchmark outcomes with a large Australian major trauma service in Melbourne. The findings are the first to report the trauma profile from a centre in the KSA and compare outcomes with an international level I trauma centre.Methods This was an observational study using records with injury dates in 2018 from the registries at both hospitals. Demographics, processes and outcomes were extracted, as were baseline characteristics. Risk-adjusted endpoints were inpatient mortality and length of stay. Binary logistic regression was used to measure the association between site and inpatient mortality.Results A total of 2436 and 4069 records were registered on the Riyadh and Melbourne databases, respectively. There were proportionally more men in the Saudi cohort than the Australian cohort (86% to 69%). The Saudi cohort was younger, the median age being 36 years compared with 50 years, with 51% of injuries caused by road traffic incidents. The risk-adjusted length of stay was 4.4 days less at the Melbourne hospital (95% CI 3.95 days to 4.86 days, p<0.001). The odds of in-hospital death were also less (OR 0.25; 95% CI 0.15 to 0.43, p<0.001).Conclusions This is the first hospital-based study of trauma in the kingdom that benchmarks with an individual international centre. There are limitations to interpreting the comparisons, however the findings have established a baseline for measuring continuous improvement in outcomes for KSA trauma services.